Tempting food words activate eating simulations - Papies, Esther K. (Frontiers in Psychology, 2013)
This study shows that tempting food words activate simulations of eating the food, including simulations of the taste and texture of the food, simulations of eating situations, and simulations of hedonic enjoyment. In a feature listing task, participants generated features that are typically true of four tempting foods (e.g., chips) and four neutral foods (e.g., rice). The resulting features were coded as features of eating simulations if they referred to the taste, texture and temperature of the food (e.g., “crunchy”; “sticky”), to situations of eating the food (e.g., “movie”; “good for Wok dishes”), and to the hedonic experience when eating the food (e.g., “tasty”). Based on the grounded cognition perspective, it was predicted that tempting foods are more likely to be represented in terms of actually eating them, so that participants would list more features referring to eating simulations for tempting than for neutral foods. Confirming this hypothesis, results showed that eating simulation features constituted 53% of the features for tempting food, and 26% of the features for neutral food. Visual features, in contrast, were mentioned more often for neutral foods (45%) than for tempting foods (19%). Exploratory analyses revealed that the proportion of eating simulation features for tempting foods was positively correlated with perceived attractiveness of the foods, and negatively with participants’ dieting concerns, suggesting that eating simulations may depend on individuals’ goals with regard to eating. These findings are discussed with regard to their implications for understanding the processes guiding eating behavior, and for interventions designed to reduce the consumption of attractive, unhealthy food.